Smuggling in the 2015 Penal Code and Implementation Precautions in Hai Phong - Truong, Le Nguyen (VNU Journal of Science: Legal Studies; Vol 34 No 4DO - 10.25073/2588-1167/vnuls.4188, 2018)
The article analyzes and discusses the amendments to the regulations on smuggling in the 2015 Penal Code in comparison with smuggling stipulated in Article 153 of the 1999 Penal Code. Thereby, the article proposes precautions to be taken for success in fighting against smuggling. Keywords: The 2015 Penal Code, smuggling, penalty. References: [1] Martin Schulz và Oliver Wasmeier (2012), The Law of Business Organizations: A Concise Overview of German Corporate Law, Nhà xuất bản Springer. [2] German Stock Corporation Act 1965. [3] Nguyễn Ngọc Hòa, Bình luận khoa học Bộ luật hình sự năm 2015, được sửa đổi, bổ sung năm 2017 (Phần chung), trang từ 13 đến trang 19. NXB Tư pháp năm 2017. [4] Báo cáo Tổng kết công tác năm 2016 của lực lượng cảnh sát điều tra tội phạm về kinh tế và tham nhũng Công an Thành phố Hải phòng, ngày 15 tháng 11 năm 2016.